PEMETAAN DATA MONOGRAFI KECAMATAN PESISIR SELATAN KABUPATEN PESISIR BARAT TAHUN 2014 - Joni Irawan; I Gede Sugiyanta; Dedy Miswar (JPG (Jurnal Penelitian Geografi), 2016)
This research aimed to create thematic maps by using Monograph Data of South Coast District in the form of data about location and number of junior and senior high school, the location of pekon government offices, the location of public offices distribution, number of population according to population density, sex ratio, number of households, acceptors, industries and the number of worship places map. This study used quasi experiment research. This research used descriptive informative.The results showed that Monograph Data of South Coast District could be presented in a map. The information was more innovative and communicative.Penelitian ini bertujuan untuk membuat peta tematik dengan memanfaatkan Data Monografi Kecamatan Pesisir Selatan berupa data tentang letak dan jumlah SMA dan SMP Negeri, letak kantor pemerintahan pekon, letak sebaran kantor pelayanan umum, jumlah penduduk berdasarkan kepadatan penduduk, sex ratio, jumlah rumah tangga, jumlah akseptor KB, jumlah industri dan jumlah tempat ibadah. Penelitian ini menggunakan metode deskriptif informatif.Hasil dalam penelitian ini adalah Data Monografi Kecamatan Pesisir Selatandapat disajikan kedalam sebuah peta.Informasi yang dituangkan lebih inovatif dan komunikatif.Kata kunci: pemetaan, data monografi kecamatan, pesisir selatan.